Calcific Uremic Arteriolopathy in Peritoneal Dialysis Populations - Nicholas New; Janaki Mohandas; George T. John; Sharad Ratanjee; Helen Healy; Leo Francis; Dwarakanathan Ranganathan (International Journal of Nephrology)
Calciphylaxis or calcific uremic arteriolopathy is an infrequent complication of end stage kidney disease. It is characterized by arteriolar medial calcification, thrombotic cutaneous ischemia, tissue necrosis often leading to ulceration, secondary infection and increased mortality rates. Current, multimodality treatment involves local wound care, well-controlled calcium, phosphate and parathyroid hormone levels and combination therapy with sodium thiosulfate and hyperbaric oxygen therapy. This combination therapy may be changing the historically poor prognosis of calcific uremic arteriolopathy reported in the literature. Peritoneal dialysis is considered a risk factor based on limited publications, however this remains to be proven. Clinical presentation, diagnosis, pathogenesis and treatment of calcific uremic arteriolopathy in these patients are no different from other patients manifesting with this condition.